2021
DOI: 10.3390/jfb12030048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resin Infiltration on Enamel: A Systematic Review and Meta-Analysis

Abstract: Subsurface enamel demineralization beneath an intact surface layer or white spots lesions (WSL) can and should be treated with non-invasive procedures to impede the development of a cavitated lesion. We aim to analyze if infiltrative resin improves enamel roughness, microhardness, shear bond strength, and penetration depth. MEDLINE [via Pubmed], Cochrane Central Register of Controlled Trials, Embase, Web of Science, Scholar, and LILACS were searched until May 2021. Methodological quality was assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 84 publications
5
36
0
13
Order By: Relevance
“…Similarly, in our study, the CAP system group showed a decline in the amount of parenchymatous defects in the teeth and maintained higher HV values than the APF group ( Figure 2 and Figure 3 ). The previous studies have also shown that when the teeth are demineralized, their microstructure changes and hardness decreases [ 16 ]; HV is used for the qualitative evaluation of the degree of enamel demineralization and is considered an indicator of tooth acid resistance in the fields of dental engineering and conservative dentistry [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, the CAP system group showed a decline in the amount of parenchymatous defects in the teeth and maintained higher HV values than the APF group ( Figure 2 and Figure 3 ). The previous studies have also shown that when the teeth are demineralized, their microstructure changes and hardness decreases [ 16 ]; HV is used for the qualitative evaluation of the degree of enamel demineralization and is considered an indicator of tooth acid resistance in the fields of dental engineering and conservative dentistry [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In different ICDAS codes, better penetration was reported in enamel lesions (ICDAS code 2–3) in contrast to the deeper lesion [ 102 ]. This was further supported by a systematic review and meta-analysis conducted by Liang et al [ 103 ] and later Soveral et al [ 82 ], where both authors described the limited ability of the resin to infiltrate deep into the dentinal lesion.…”
Section: Present: Clinical Usage and Limitations Of The Current Rimentioning
confidence: 77%
“…High patient satisfaction has been reported following the infiltration of WSL [ 79 , 80 ]. Further, infiltration improves the surface microhardness [ 81 ] and shear bond strength while reducing the surface roughness of the infiltrated WSL [ 82 ].…”
Section: Present: Clinical Usage and Limitations Of The Current Rimentioning
confidence: 99%
“…In addition to their preserving feature due to little to no preparation required, resin composites also provide excellent esthetics in the anterior region [ 19 ]. It is known that the application of resin infiltration increases the bond strength between the white spot lesions and the resin composite [ 20 ]. Therefore, it can be said that it is a rational method to support resin composites in places where the resin infiltration method is insufficient.…”
Section: Discussionmentioning
confidence: 99%